2018
DOI: 10.15171/ijoem.2018.1197
|View full text |Cite
|
Sign up to set email alerts
|

Association between Metabolic Syndrome and Job Rank

Abstract: Background: The occupation of the people can influence the development of metabolic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
(27 reference statements)
1
10
0
1
Order By: Relevance
“…However, the association of MetS risk with not only occupation type but also SES must be determined. 22 32 34 35 SES is a concept encompassing salary, social status and education and can be indicated by an individual’s occupation. 36 Al-Thani et al 34 and Mehrdad et al 22 reported that occupation type and seniority in a company, respectively, are not significantly associated with MetS risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the association of MetS risk with not only occupation type but also SES must be determined. 22 32 34 35 SES is a concept encompassing salary, social status and education and can be indicated by an individual’s occupation. 36 Al-Thani et al 34 and Mehrdad et al 22 reported that occupation type and seniority in a company, respectively, are not significantly associated with MetS risk.…”
Section: Introductionmentioning
confidence: 99%
“… 22 32 34 35 SES is a concept encompassing salary, social status and education and can be indicated by an individual’s occupation. 36 Al-Thani et al 34 and Mehrdad et al 22 reported that occupation type and seniority in a company, respectively, are not significantly associated with MetS risk. Therefore, this study conducted in Taiwan focused on the relationship of type of occupation with MetS prevalence as well as with the biochemical indexes of related chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of MetS had significantly increased amongst female blue-collar workers, those with lower education level and household income 16 . Part-time or temporary workers of either gender showed higher MetS prevalence than full-time workers 16 , but job rank was not associated with MetS in Mehrdad et al study 18 . The prevalence of MetS significantly augmented with being married 16 , and smoking status 16,19 .…”
Section: Demographic and Social Risk Factors Related To Metabolic Synmentioning
confidence: 75%
“…The estimated prevalence of metabolic syndrome (MetS) is 9.5% in machine operators and 7.5–10.6% in Dutch trade workers [ 4 ]. In Taiwan, 7.7% of labourers [ 5 ], 8.2% of high-tech labour [ 1 ], and 10.3% of hospital employees [ 6 ] meet the criteria for metabolic syndrome. According to the Health Promotion Hospital (HPH) trend, the health of hospital employees is a matter of great concern for hospital management.…”
Section: Introductionmentioning
confidence: 99%